Research on microstructure and mechanical properties of HIP Ti-6Al-4V treated by surface rolling at low-heating temperatures. (30th October 2020) - Li, Gang; Zhang, Wenkang; Liu, Yu; Xue, Chuan; Ma, Yan; Yuan, Hengyi
Abstract: This paper was to research the effects of surface rolling at low-heating temperatures (SRLT) on microstructure and mechanical properties of HIP Ti–6Al–4V alloy. An obviously plastic deformation emerged in surface modification layer and accompanied with the grain refinement and dense dislocations. The values of compressive residual stress and surface microhardness were also increased. The fretting friction tests were further compared without lubrication. The sample treated by surface rolling (SR) at 160 °C had the smaller steady-state CoF and less material loss relative to the untreated sample. But it still had the higher steady-state Coefficient of friction (CoF) and more material loss than surface-rolled sample at room temperature. On the one hand, the comparatively low microhardness and residual stress would damage the mechanical properties. On the other hand, the material's friction would be increased by the high surface roughness and the absence of cold work strengthening would decrease the wear resistance. In addition, the low-heating temperature would also increase material deformation mechanism and decline the friction properties.